Sinus metastasis of lung adenocarcinoma: a case report - Xu, Mingyuan; Sun, Qi; Lv, Xin; Chen, Fangjun; Su, Shu; Wang, Lifeng (Frontiers in Medicine, 2024)
Metastatic carcinoma of the paranasal sinuses in lung cancer is an extremely uncommon condition. We report here a 57-year-old female patient with epidermal growth factor receptor (EGFR)-positive stage IV non-small cell lung cancer (NSCLC) with multiple bone metastases. After resistance to second- and third-generation EGFR-tyrosine kinase inhibitors (TKIs), the patient presented with headache accompanied by progressively enlarging lesions of the nasal cavity on CT scan. Further endoscopic sinus neoplasmectomy confirmed sinus metastasis of lung adenocarcinoma. Although subsequent chemotherapy and immunotherapy were both administered, the disease continued to progress, and the patient passed away 21 months after diagnosis. Combined with real-time dynamic next-generation sequencing (NGS) during the different generations of EGFR-TKI treatments and dynamic tumour microenvironment analysis, we discussed the clinical manifestations of sinus metastasis and the molecular biology and tumour immune microenvironment changes after resistance to the second-and third- generation of EGFR-TKI therapy.